A dislocation density-based model for the temperature dependent anomalous behaviors of nickel-based single-crystal superalloy. (July 2022) - Lu, Pin; Ge, Yuxue; Jin, Xiaochao; Li, Pan; Ji, Xinkuo; Zhao, Dan; Wang, Zhihua; Fan, Xueling
Abstract: A dislocation density-based single crystal plasticity constitutive model was developed to capture the temperature dependent anomalous yield and tension/compression asymmetry behavior of nickel based single crystals. Firstly, the mathematical description of physical mechanism of anomalous yield behavior was considered in the hardening rules, i.e. thermally activated cross-slip mechanism. Secondly, a temperature dependent function was established to describe the transformation of dislocation motion mode from shearing to by-passing. Thirdly, three non-Schmid stress tensors were introduced into the constitutive model to describe the tension/compression asymmetric phenomenon. The model considers the contributions of various strengthening mechanisms, including solid solution, precipitates and base metal. Furthermore, the evolution of microstructural features (such as dislocation density, etc.) and contribution of each mechanism to yield stress with increasing temperature were further analyzed. The model has been implemented via crystal plasticity framework and can predict the temperature dependent anomalous characteristics of yield stress of Ni-based single crystal. Graphical abstract: Image 1 Highlights: A new dislocation-density based crystal plasticity model is developed for DD6 alloy. Both anomalous yield behavior and tension/compression asymmetry are taken into account. The transition of dislocation motion mode from shearing to by-passing is incorporated in the hardening rule. The intermediate temperature brittleness was considered in constitutive model.